Factors influencing Tanzanian mothers’ feeding practices for toddlers: A predictive correlational study - Debora Dyson Bukuku; Tassanee Prasopkittikun; Sudaporn Payakkaraung; Chayapa Lenwari (Belitung Raya Foundation, Indonesia, 2023)
Background: Feeding practices are crucial in ensuring toddlers receive an appropriate and varied diet to support their growth and development. In Tanzania, maternal feeding practices for young children are inadequate, and there is limited research on the influencing factors. Objective: This study aimed to examine the factors influencing Tanzanian mothers’ feeding practices for toddlers, utilizing the health promotion model as the theoretical framework. Methods: A predictive correlational design was employed, with a random sample of 399 mothers who brought their toddlers for health supervision at a tertiary care hospital in the United Republic of Tanzania. Data on personal information, depression, perceived benefits, perceived barriers, perceived self-efficacy, social support, situational influences, and maternal feeding practices were collected using self-administered questionnaires between September 2021 and November 2021. Descriptive statistics, correlations, and multiple regression analysis were employed for the analysis. Results: All the factors examined in the study accounted for 18.9% of the variance explained in maternal feeding practices. Significantly, only two factors, perceived self-efficacy (β = 0.32, p <0.001) and situational influences (β = 0.24, p <0.001), could predict maternal feeding practices. Conclusion: Perceived self-efficacy and situational influences emerged as the primary influencing factors on maternal feeding practices for toddlers. Pediatric nurses should address these modifiable factors when developing nursing interventions and strategies to promote a healthy nutritional status in toddlers.